Responsabilidad social corporativa y su incidencia en el cumplimiento de la normativa empresarial en el sector terciario, Cantón Quevedo, 2023 - Bustos Laiño , Diana Mishell (2024)
In Canton Quevedo during the year 2023, a comprehensive study was conducted on the impact of Corporate Social Responsibility (CSR) and its impact on through compliance with business regulations in the tertiary sector. The research aimed to establish guidelines for promoting CSR in companies in the region. Using a quantitative, analytical and descriptive methodology, we identified obstacles and challenges in this sector, examined regulatory compliance and assessed the gap between companies and CSR. Observation and survey of 267 business owners in the city's tertiary sector were key tools in the data collection process. Business compliance plays a crucial role in promoting ethical and sustainable practices. Companies that take proactive measures to comply with regulations demonstrated 80% of the strongest commitment to social responsibility, generating positive impacts both in the business environment and in society in general. The results showed aspects that can be improved in the long term, such as increased compliance with business regulations. There was little awareness of the importance of CSR, but there was also a stronger willingness to implement responsible practices. These findings suggest that the tertiary sector in Cantón Quevedo during the year 2023 is moving towards a more ethical and sustainable business model, which bodes well for the economic and social development of the region.